2021
DOI: 10.1523/jneurosci.0284-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Augments Dopamine-Mediated Inhibition of Neuronal Activity in the Dorsal Bed Nucleus of the Stria Terminalis

Abstract: The dorsal region of the bed nucleus of the stria terminalis (dBNST) receives substantial dopaminergic input which overlaps with norepinephrine input implicated in stress responses. Using ex vivo fast scan cyclic voltammetry in male C57BL6 mouse brain slices, we demonstrate that electrically stimulated dBNST catecholamine signals are of substantially lower magnitude and have slower uptake rates compared with caudate signals. Dopamine terminal autoreceptor activation inhibited roughly half of the catecholamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…A second problem is that, unlike ionotropic excitatory or inhibitory connections, there is much less known about the ultrastructural characteristics of potential DA synapses, where they occur on neurons, or how frequently ( Liu et al, 2018 ; Rice and Cragg, 2008 ). Thus, analyzing DA circuits has required specific labeling, either with immunohistochemistry ( Bérubé-Carrière et al, 2012 ; Moss and Bolam, 2008 ; Omelchenko and Sesack, 2009 ; Liu et al, 2018 ) or with genetic targeting ( Dos Santos et al, 2018 ; Melchior et al, 2021 ; Mingote et al, 2019 ; Nasirova et al, 2021 ; Poulin et al, 2018 ). However, fundamental questions remain unanswered: (1) how often do DA axons make synapses that appear like classic chemical synapses (i.e., with synaptic vesicles and post-synaptic densities [PSDs]), (2) where do DA synapses occur on target neurons, (3) what do DA axonal varicosities contain, and (4) are there signs of other physical interactions between DA axons and their targets?…”
Section: Introductionmentioning
confidence: 99%
“…A second problem is that, unlike ionotropic excitatory or inhibitory connections, there is much less known about the ultrastructural characteristics of potential DA synapses, where they occur on neurons, or how frequently ( Liu et al, 2018 ; Rice and Cragg, 2008 ). Thus, analyzing DA circuits has required specific labeling, either with immunohistochemistry ( Bérubé-Carrière et al, 2012 ; Moss and Bolam, 2008 ; Omelchenko and Sesack, 2009 ; Liu et al, 2018 ) or with genetic targeting ( Dos Santos et al, 2018 ; Melchior et al, 2021 ; Mingote et al, 2019 ; Nasirova et al, 2021 ; Poulin et al, 2018 ). However, fundamental questions remain unanswered: (1) how often do DA axons make synapses that appear like classic chemical synapses (i.e., with synaptic vesicles and post-synaptic densities [PSDs]), (2) where do DA synapses occur on target neurons, (3) what do DA axonal varicosities contain, and (4) are there signs of other physical interactions between DA axons and their targets?…”
Section: Introductionmentioning
confidence: 99%
“…Indistinguishable catecholamine redox potentials present a major limitation of in vivo electroanalytical methods, including FSCV, to selectively measure NE or DA in target brain areas/tissues with substantial innervation of both catecholamines. Importantly, our and other prior pharmacological, neurochemical, and histological evidence established that NE is the predominant catecholamine in the v BNST for the past decade as described in the Introduction , (for review, see ref ).…”
Section: Resultsmentioning
confidence: 54%
“…Although FSCV has widely been applied to DA rich brain regions for the study of their roles in drug use disorders and mental disorders, fewer studies have incorporated FSCV to investigate NE in vivo . Our and other labs have shown that the major catecholamine in the ventral ( v ) BNST is NE (>92%), while other subregions of the BNST (e.g., dorsal and lateral) receive both NE and DA innervation, as demonstrated through neurochemical, pharmacological, and anatomical evidence , (for review, see ref ). Herein, we determined in anesthetized male rats how d- and l-METH modulate both NE and DA regulation.…”
Section: Introductionmentioning
confidence: 91%
“…Our result positions BNST in the encoding of CS’s motivational properties, and such a role is likely to be amplified by BNST’s descending connections with VTA. BNST both sends and receives robust projections to and from VTA GABA and DA neurons, which enable BNST to exert a direct influence over DA release (Melchior et al, 2021 ; Yu et al, 2021 ). VTA-projecting BNST neurons are overwhelmingly GABAergic and these neurons preferentially synapse onto VTA GABA neurons.…”
Section: Discussionmentioning
confidence: 99%